2016
DOI: 10.1111/ffe.12475
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of specific contribution of residual stress generated near surface anomalies in the high temperature fatigue life of a René 65 superalloy

Abstract: This study evaluates the influence of residual stresses induced by the fabrication of surface anomalies on the fatigue crack growth in a nickel based superalloy. To separate the notch effect of the geometry from the residual stress field induced by fabrication of the surface flaws, two V‐type anomalies are considered: scratches and dents with equivalent morphology and size. A specially designed heat treatment has been used to reduce the magnitude of residual stresses around these anomalies in order to highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The effects of handling and service damage on the fatigue life of components is frequently estimated by empirical methods or ignored altogether. The work of Gourdin et al (2014Gourdin et al ( , 2016 on crack propagation near surface anomalies is one of the few references to handling damage in the literature. Currently, a crack propagation analysis of components with small scratches and dents is frequently made by assuming the damage geometry to be an initial crack of same length and depth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of handling and service damage on the fatigue life of components is frequently estimated by empirical methods or ignored altogether. The work of Gourdin et al (2014Gourdin et al ( , 2016 on crack propagation near surface anomalies is one of the few references to handling damage in the literature. Currently, a crack propagation analysis of components with small scratches and dents is frequently made by assuming the damage geometry to be an initial crack of same length and depth.…”
Section: Introductionmentioning
confidence: 99%
“…Using the potential drop technique, Gourdin et al (2016) quantified the difference in crack initiation and propagation time between scratches and dents of similar geometry. Experiments were undertaken in the presence and absence of residual stresses; the latter achieved by a thermal treatment of the specimens in order to relax the residual stresses.…”
Section: Introductionmentioning
confidence: 99%
“…The evidences indicate the scratch has an important role to initiate fatigue crack on blade root chamfer. Gourdin 5 found that the fatigue crack growth of natural cracks initiating from scratches without residual stresses is identical and similar to the long crack growth behavior of a nickel based superalloy. Inchekel and Talia 6 revealed that the fatigue life decreased sharply as the scratch depth increased and an edge scratch is more detrimental than a center scratch.…”
mentioning
confidence: 72%
“…It has also been shown that crack initiation in samples with surface damage is influenced by the same three factors suggested in [5]. In the work of Gourdin et al [9,10], the effect of scratches and dents on crack initiation and propagation was assessed by using a potential drop technique.…”
Section: Introductionmentioning
confidence: 97%